2021
DOI: 10.3390/jcm10020179
|View full text |Cite
|
Sign up to set email alerts
|

Women with a History of Recurrent Pregnancy Loss Are a High-Risk Population for Adverse Obstetrical Outcome: A Retrospective Cohort Study

Abstract: Recurrent pregnancy loss (RPL), defined as three or more consecutive miscarriages, is hypothesized to share some of the same pathogenic factors as placenta-associated disorders. It has been hypothesized that a defect implantation causes pregnancy loss, while a partially impaired implantation may lead to late pregnancy complications. The aim of this retrospective register-based cohort study was to study the association between RPL and such disorders including pre-eclampsia, stillbirth, small for gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
2
10
1
Order By: Relevance
“…Also, we found no association between low p-MBL levels and the incidence of preterm birth and low BW, although the latter analyses were based on very few observations. Nonetheless, the frequency of preterm birth after RPL in our patients corresponds to the frequency of 10.0% reported in a large Swedish register study ( Rasmark Roepke et al , 2021 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also, we found no association between low p-MBL levels and the incidence of preterm birth and low BW, although the latter analyses were based on very few observations. Nonetheless, the frequency of preterm birth after RPL in our patients corresponds to the frequency of 10.0% reported in a large Swedish register study ( Rasmark Roepke et al , 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…A significantly increased incidence of preterm birth, reduced birth weight (BW) and other perinatal complications is found in RPL patients ( Basso et al , 1998 ; Jivraj et al , 2001 ; Brown et al , 2008 ; Dempsey et al , 2014 ; Field and Murphy, 2015 ; Rasmark Roepke et al , 2021 ). Since low p-MBL levels may be associated with RPL, an obvious question is whether an aberrant p-MBL level is associated with a negative reproductive prognosis and an increased risk for adverse perinatal outcomes in RPL patients?…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Chronic hypertension did not constitute an exclusion criteria for RPL cases and control women. Unlike gestational hypertension (preeclampsia), which is a confirmed risk factor for pregnancy complications, 32,33 including RPL, chronic hypertension was not linked with adverse pregnancy complications. 34 Furthermore, we demonstrated that the association of the investigated FOXP3 variants with RPL was not affected by parity, as the allelic and genotypic distribution of rs2294021, rs2232365, and rs3761548 SNPs was comparable between nulliparous (no live births) and multiparous (one or more live births) RPL cases.…”
Section: As Foxp3 Controls Treg Cells Development and Function And As...mentioning
confidence: 87%
“…29 Our results were also contradictory to two independent Chinese (Han) studies, which reported no association of rs2294021 minor allele or genotypes with RPL. 27,32 These apparently contradictory findings are explained by case and control selection criteria, the ethnic background of study participants, and even differences in genotyping methods. 29 While not addressed here, epigenetic alteration, [33][34][35] including Foxp3 hypermethylation, 35 may increase the risk of RPL, in part through decreasing the number of Treg cells.…”
Section: As Foxp3 Controls Treg Cells Development and Function And As...mentioning
confidence: 99%
“…Reproductive loss is common, occurring in up to a quarter of all pregnancies, and recurrent pregnancy loss is also related to subsequent neonatal morbidity and mortality. 1,2 Parents experiencing difficulty grappling with an infant enduring significant morbidity in the intensive care are more likely to have experienced reproductive loss or issues with infertility. 3 Additionally, advanced maternal age, multiple gestation pregnancies, and reproductive technology have been linked to increased neonatal morbidity and mortality.…”
Section: Fundamentals O F Reproductive Loss a N D Traumamentioning
confidence: 99%